A MEDIUM CONTAINING COMMERCIAL FOLIAR FERTILIZER AND SOME ORGANIC ADDITIVES COULD SUBSTITUTE MS MEDIUM FOR IN VITRO GROWTH OF DENDROBIUM HYBRID SEEDLINGS - Dwi Hapsoro Hapsoro; Vincentia Atika Septiana Septiana; Sri Ramadiana Ramadiana; Yusnita yusnita (Jurnal Floratek, 2018)
In an attempt to obtain a cost-effective and a simpler way of growing Dendrobium seedling in vitro, this study was conducted to investigate effects of basal media and organic additives on in vitro growth of Dendrobium seedlings.  The basal media used were that of half strength Murashige and Skoog (½ MS medium) and that containing foliar fertililizer 32:10:10 and trace elements (FT medium). Treatments were combinations of basal media (1/2 MS medium and FT medium) and different kinds of organic additive (tomato, potato, and mungbean sprout juice and banana homogenate). The experiment was conducted in a completely randomized design with three replicates, 5 culture vessels per replicate and 4 seedlings ca. 1.5 cm per vessel.  The experiment showed that FT medium resulted in significantly higher growth than ½ MS medium as indicated by seedling fresh weight.  The media containing tomato juice led to highest growth of seedling as shown by seedling fresh weight and seedling height. Since FT medium caused better growth than ½ MS medium, the FT medium could be used as a substitute for ½ MS medium for growing Dendrobium hybrid seedlings. The seedlings were successfully acclimatized in a shaded green house environment with 100% survival rate.